Development of pencak silat gym learning (Universitas Negeri Semarang, 2022)
This research is a development research, namely the development of pencak silat gym learning for students at the University of PGRI Palembang. The development of this learning model aims to obtain a varied learning model that can be applied by students. This research was conducted at the University of PGRI Palembang, in 2021. The research subjects were students who took the pencak silat course in the Physical Education study program, Faculty of Teacher Training and Education. The research method used is the Research and Development (R D) method adopting the Borg and Gall theory to the Operational Product Revision stage. The research instrument is a product appraisal questionnaire. The results of this study are the Pencak Silat)gymnastics learning model which consists of 17 movements, core 30 movements, and cooling down 9 movements. The media expert validation data obtained from the product display aspect got a score of 80.00% and the audio/music aspect used got a score of 93.33%, the development results from the video content aspect got 92.73%, the user alternative media aspect got 80.00% , expert validation of the quality aspect of the gymnastics material got a score of 93.33% and the content aspect of the gymnastics got 92.00%, while the results of the development of the quality aspect of the pencak silat material got 86.67% and the content aspect of pencak silat got 96.00%. In the small-scale test, the student's response to this product from the appearance aspect got a score of 86.13% and the material/content aspect got a score of 87.20%. In the large-scale test, the student's response to this product from the appearance aspect got a score of 87.00% and the material/content aspect got a score of 88.80%. And it can be concluded that the product is feasible to be applied.